Calcium-Activated Chloride Channel ANO1/TMEM16A: Regulation of Expression and Signaling - Dulin, Nickolai O. (Frontiers in Physiology, 2020)
Anoctamine-1 (ANO1), also known as TMEM16A is the most studied member of anoctamin family of calcium-activated chloride channels with diverse cellular functions. ANO1 controls cell volume, proliferation, survival, migration, contraction and secretion. This review summarizes the current knowledge of mechanisms governing the regulation of ANO1 expression and ANO1-induced intracellular signaling.